Elearning levels - Baskas, Antanas (Lietuvos matematikos rinkinys, 2023)
For most institutions information technologies represent a hole of additional expense. Most campuses have simply bolted new technologies onto a fixed plant, a fixed faculty, and a fixed notion of classroom instruction. Presented results show that all thirty institutions of course redesign online learning program reduced cost by about forty percent on average, increased course-completion rates, improved retention, better student attitudes toward the subject matter. All universities and colleges of this program have realized promise of technology by means of whole course redesign, active learning, computer-based learning resources, mastery learning, on-demand help, alternative staffing.